2019
DOI: 10.1155/2019/1932503
|View full text |Cite
|
Sign up to set email alerts
|

Acute Postexercise Change in Circulating Irisin Is Related to More Favorable Lipid Profile in Pregnant Women Attending a Structured Exercise Program and to Less Favorable Lipid Profile in Controls: An Experimental Study with Two Groups

Abstract: Introduction. The blood irisin concentrations may be affected both by exercise and pregnancy. We aimed to determine acute responses in serum irisin after a single exercise session and relationships between exercise-induced changes in this hormone and lipid profile in pregnancy. Material and Methods. It was an experimental study in 20 Caucasian women in normal pregnancy (age 30±3 years, 28±6 weeks of gestation; mean±SD). Participants were assigned to training (n=8) and control groups (n=12). Before the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Due to evidence that the irisin concentration may vary significantly depending on the utilized type of commercial kit, comparison of the results is possible only with studies that use the same type of kit. The average pre-exercise irisin level was consistent with the baseline level found in healthy individuals in the KarMeN-study [32], in a study of adipose women of a similar age reported by Winn et al [33], a middle aged Chinese population [34], and even similar to the values measured in pregnant women between the second and third trimester of normal gestation [35]. However, the values that we report in the current study were almost 40 times lower than the baseline plasma irisin level determined in a small study sample of similar characteristics in Norway [20], and slightly lower than the baseline level detected in a group of adolescents [36].…”
Section: Discussionsupporting
confidence: 88%
“…Due to evidence that the irisin concentration may vary significantly depending on the utilized type of commercial kit, comparison of the results is possible only with studies that use the same type of kit. The average pre-exercise irisin level was consistent with the baseline level found in healthy individuals in the KarMeN-study [32], in a study of adipose women of a similar age reported by Winn et al [33], a middle aged Chinese population [34], and even similar to the values measured in pregnant women between the second and third trimester of normal gestation [35]. However, the values that we report in the current study were almost 40 times lower than the baseline plasma irisin level determined in a small study sample of similar characteristics in Norway [20], and slightly lower than the baseline level detected in a group of adolescents [36].…”
Section: Discussionsupporting
confidence: 88%
“…Third, we only investigated serum irisin once in 30 min after IS, so the results do not represent the overall irisin response during the recovery period after IS. However, the reason for this design was to reduce the effect of the irisin circadian rhythm on the results ( Anastasilakis et al, 2014 ), and it has reported that 30 min is the sufficient time for stimulation irisin secretion by exercise or cryostimulation intervention ( Huh et al, 2012 ; Dulian et al, 2015 ; Szumilewicz et al, 2019 ). Lastly, no data on metabolic disorders, the time interval between lunch and IS, diet on the test day, cardiorespiratory fitness measurements, or detection of in vivo metabolic parameters were included in our study, so we could not adjust for metabolic pathologies or feeding effects that may associated with energy balance and the evaluation of macronutrients status to distinguish the exact metabolic states of the Δirisin− and Δirisin + groups.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal oxygen consumption during exercise was measured during a progressive maximal test on a cycloergometer with electronically regulated load (Viasprint 150P) and respiratory gas analyzer (Oxycon Pro, Erich JAEGER GmbH, Germany). We presented the test protocol in our previous study [ 53 ]. As maximal oxygen capacity (VO 2 max) we treated the highest value of oxygen uptake, which was maintained for 15 s. The anaerobic threshold (AT) values, such as oxygen uptake at AT (VO2/AT) and heart rate at AT (HR/AT) were established using the V-slope method [ 54 ].…”
Section: Methodsmentioning
confidence: 99%